-6(7-2x)=5x-21

Simple and best practice solution for -6(7-2x)=5x-21 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(7-2x)=5x-21 equation:


Simplifying
-6(7 + -2x) = 5x + -21
(7 * -6 + -2x * -6) = 5x + -21
(-42 + 12x) = 5x + -21

Reorder the terms:
-42 + 12x = -21 + 5x

Solving
-42 + 12x = -21 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
-42 + 12x + -5x = -21 + 5x + -5x

Combine like terms: 12x + -5x = 7x
-42 + 7x = -21 + 5x + -5x

Combine like terms: 5x + -5x = 0
-42 + 7x = -21 + 0
-42 + 7x = -21

Add '42' to each side of the equation.
-42 + 42 + 7x = -21 + 42

Combine like terms: -42 + 42 = 0
0 + 7x = -21 + 42
7x = -21 + 42

Combine like terms: -21 + 42 = 21
7x = 21

Divide each side by '7'.
x = 3

Simplifying
x = 3

See similar equations:

| 6n=2n+12 | | -(a+2)=5 | | 2r=r+3 | | -10+4=2 | | 4x+48=112 | | 4r-7=37 | | 9x+27=9(x+w)+9 | | -38=x-20 | | 8m(4m+1)=170 | | (3-4)-(2+4*3)=-6+5*3 | | 1.5x-3=12 | | 11+8x=01 | | 54-3x=x^2 | | -4(x-5)+2=-20x+22 | | 3(3+4)=3*3+4 | | -8(m-5)=25-5m | | (3)(4)(x)=6 | | 8mx(4m+1)=170 | | -6b(5a-2b)-7(-3ab-4b^2)= | | 45q-32=70q-82 | | a+18=23 | | -2x-6=2-4x-(-x-1) | | (G+8)=2X+H | | 11(x-5)=(x+5) | | -21=2x-9 | | 191-v=89 | | -3(r+6)=-58 | | 3x+2=3(4)+2 | | 4y-4=35-6y | | z^4=28+96i | | 2x-18=3x+8 | | 231=165-y |

Equations solver categories